Transportable open-source application program interface and user interface for generic humanoids: TOUGH. (5th May 2020) - Jagtap, Vinayak; Agarwal, Shlok; Wagh, Ameya; Gennert, Michael
Humanoid robotics is a complex and highly diverse field. Humanoid robots may have dozens of sensors and actuators that together realize complicated behaviors. Adding to the complexity is that each type of humanoid has unique application program interfaces, thus software written for one humanoid does not easily transport to others. This article introduces the transportable open-source application program interface and user interface for generic humanoids, a set of application program interfaces that simplifies the programming and operation of diverse humanoid robots. These application program interfaces allow for quick implementation of complex tasks and high-level controllers. Transportable open-source application program interface and user interface for generic humanoids has been developed for, and tested on, Boston Dynamics' Atlas V5 and NASA's Valkyrie R5 robots. It has proved successful for experiments on both robots in simulation and hardware, demonstrating the seamless integration of manipulation, perception, and task planning. To encourage the rapid adoption of transportable open-source application program interface and user interface for generic humanoids for education and research, the software is available as Docker images, which enable quick setup of multiuser simulation environments.